(untitled) (Journal of Scientific Research, 2014)
Six marketed oral antidiabetic metformin tablets in Bangladesh have been studied for their drug content, release profile and glucose lowering capacities. This sort of study is a good indicator for in vivo evaluation of the quality of an oral antidiabetic preparation. Marketed preparations of metformin-HCl from different manufacturers were randomly chosen for this study. The drug content was within the United State Pharmacopoeia (USP) specified limit (95-105%) in all cases. The blood glucose levels were investigated in streptozotocin-induced diabetic rats (SIDRs) after 5 hours of single dose (110 mg/kg body weight) treatment of the products; significantly (p<0.05) reduced blood glucose level by 58.1, 53.2, 50.8, 77.0, 72.9 and 49.1%, respectively; which were consistent with antihyperglycemic effects of standard metformin-HCl (71.3%). All the products were found to be qualified in lowering blood glucose level. It may be inferred that the metformin-HCl tablets of Bangladeshi manufacturers complies with the standard specifications for drug contents, dissolution and antihyperglycemic properties. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i3.19290 J. Sci. Res. 6 (3), 581-588 (2014)